REPRESENTASI KEHIDUPAN PEREMPUAN URBAN DALAM NOVEL WINTER IN TOKYO KARYA ILANA TAN - Hidayah, Nurul; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2019)
This study aims to describe representations of: (1) personality pleasures, (2) recreational prestige, (3) mobility lifestyles, (4) instant culture in the Winter In Tokyo novel by Ilana Tan. The data of this study are the story elements of the Winter In Tokyo novel by Ilana Tan. The data source for this study is the Winter In Tokyo novel by Ilana Tan. There are four stages to collecting data. First, read the Winter In Tokyo novel by Ilana Tan. Second, do library research. Third, look for and record data related to research problems. Based on the results of the study concluded: (1) urban communities have personality pleasures, (2) urban communities have recreational prestige, (3) the level of mobility of urban communities is high, (4) urban communities have an instant lifestyle that is increasingly high.Keywords: urban societies, metropop novel, personality pleasures, mobility, recreational prestige, instant.